1997
DOI: 10.1046/j.1365-2796.1997.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic role of hyaluronan (HYA) in connective tissue activation and inflammation

Abstract: Gerdin B, Hällgren R (University Hospital, Uppsala, Sweden). Dynamic role of hyaluronan (HYA) in connective tissue activation and inflammation (Minisymposium: Hyaluronan). J Intern Med 1997; 242: 49–55. An increased tissue accumulation of HYA occurs in several human and experimental inflammatory conditions. Such is the case in sarcoidosis, idiopathic pulmonary fibrosis and farmer's lung in man, and experimental bleomycin‐induced lung damage in rats. Graft rejection in man and rats, experimental myocarditis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 41 publications
4
97
0
3
Order By: Relevance
“…Inflammation, infection, or physical damage can lead to the release of soluble GAGs. An inflammatory reaction, irrespective of its cause, is followed by increased synthesis of HA in the interstitium (30). GAGs are secreted during the activation of various cells, for example, endothelial and T cells (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation, infection, or physical damage can lead to the release of soluble GAGs. An inflammatory reaction, irrespective of its cause, is followed by increased synthesis of HA in the interstitium (30). GAGs are secreted during the activation of various cells, for example, endothelial and T cells (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…An inflammatory reaction, irrespective of its cause, is followed by increased synthesis of HA in the interstitium (30). GAGs are secreted during the activation of various cells, for example, endothelial and T cells (30,31). Furthermore, bacterial pathogens display GAGs or GAG-like polysaccharide antigens on their surfaces, for example, group A streptococci possess an HA-rich capsule (32).…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronan accumulates in the extracellular matrix and in serum in many inflammatory states, and often the serum level correlates with the degree of inflammation (6,7). Several studies have demonstrated that activated leukocytes can bind to endothelial cell HA (8 -12), and we recently demonstrated that leukocytes can bind to virally infected SMCs via novel structures formed by HA (13,14).…”
mentioning
confidence: 99%
“…Endogenous HMW HA plays a pivotal role in the homeostasis of the upper and the lower airways: it is an important component of the normal airway secretions, exerts anti-inflammatory and antiangiogenic actions, promotes cell survival and mucociliary clearance, organizes extracellular matrix, stabilizes connective tissues, sustains healing processes and regulates tissues hydration [144,[232][233][234]. Hence, exogenous HMW HA represents a promising therapeutic agent for the treatment of nasal and lung diseases that involve inflammation, oxidative stress and epithelial remodeling, such as allergic and non-allergic rhinitis, asthma, chronic obstructive pulmonary disease and cystic fibrosis [143,233,[235][236][237][238].…”
Section: Rhinology and Pneumologymentioning
confidence: 99%